1993
DOI: 10.1002/1097-0142(19930715)72:2<418::aid-cncr2820720217>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum neural cell adhesion molecule as a new tumor marker in small cell lung cancer

Abstract: Background. Small cell lung cancer (SCLC) is distinguished from other histologic types of lung cancer by possessing a variety of neuroendocrine properties. Neuron‐specific enolase (NSE) is the most frequently elevated tumor marker for patients with SCLC at diagnosis. To assess the value of neural cell adhesion molecules (NCAM), another possible tumor marker for small cell lung cancer, NCAM was evaluated in the sera of patients with histologically confirmed SCLC in two prospective multicenter trials. Methods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Similarly, NCAM is consistently expressed in neuroendocrine lung cancer cells and has also been described as a tumor-marker protein for SCLC. 24 We have detected NCAM transcripts in blood samples of 10 negative control patients, which is in congruence with the literature describing the expression of NCAM-140, the most prevalent NCAM isoform in SCLC, in natural killer cells as well. 25,26 Highly sialylated isoforms of NCAM preferentially occur during embryogenesis but also in SCLC, where they have been hypothesized to confer aggressive growth properties and a higher metastatic potential.…”
Section: Detection Of Lung Cancer Cells In Sputum Samplessupporting
confidence: 89%
“…Similarly, NCAM is consistently expressed in neuroendocrine lung cancer cells and has also been described as a tumor-marker protein for SCLC. 24 We have detected NCAM transcripts in blood samples of 10 negative control patients, which is in congruence with the literature describing the expression of NCAM-140, the most prevalent NCAM isoform in SCLC, in natural killer cells as well. 25,26 Highly sialylated isoforms of NCAM preferentially occur during embryogenesis but also in SCLC, where they have been hypothesized to confer aggressive growth properties and a higher metastatic potential.…”
Section: Detection Of Lung Cancer Cells In Sputum Samplessupporting
confidence: 89%
“…With regard to current biomarkers used in the clinic, this is the expected concentration range, giving us hope that new lung cancer markers should be detectable in serum. Through our method, we successfully identified proteins that are putative or currently used as biomarkers of lung cancer, including CEA (27,28), pro-GRP (29,31), SCC antigen (47,48), tumor M2-PK (49), NCAM (35)(36)(37), chromogranin A (29), and chromogranin B (30). In addition, we identified putative markers previously reported in lung-related proteomics studies such as member C1 of aldo-keto reductase family 1 identified by Huang et al (25) as dihydrodiol dehydrogenase and matrix metallopeptidase 1 found to be overexpressed in lung cancer patients and especially in late stage (18).…”
Section: Discussionmentioning
confidence: 99%
“…In adult patients, serum polysialylated NCAM levels above 20 kU 1-' have been shown to be pathological (Jaques et al, 1993;Kaiser et al, 1994). We found levels of up to 62.9 kU 1-l in healthy children in whom the levels are on average higher (mean 26.8 kU 1-') than in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Recently. it has been shown that the serum levels of polysialylated NCAM are elevated in adult patients with small-cell lung cancer (Jaques et al 1993) and multiple myeloma (Kaiser et al 1994). high levels being associated with a poor prognosis (Ledermann et al 1994: Smith et al, 1996.…”
mentioning
confidence: 99%